Work motivation and job satisfaction of health workers in urban and rural areas - Grujičić, Maja; Jovičić Bata, Jelena; Rađen, Slavica; Novaković, Budimka; Šipetić Grujičić, Sandra (Vojnosanitetski pregled, 2017)
Background/Aim. Motivated and job satisfied health professionals represent a basis of success of modern health institutions. The aim of this study was to investigate whether there was a difference in work motivation and job satisfaction between health workers in urban and rural areas in the region of Central Serbia. Methods. The study included 396 health professionals from urban setting, and 436 from a rural area, employed in four randomly selected health facilities. An anonymous questionnaire was used for data gathering. Statistical analysis was performed using χ2, Student t-test, Spearman’s correlation coefficient, and logistic regression analysis. Results. Urban health professionals were significantly more motivated and job satisfied than respondents from rural area. In relation to work motivation factors and job satisfaction of health professionals in urban and rural areas, there were no significant differences in working conditions and current equipment, and in terms of job satisfaction there were no significant differences in relation to income either. Conclusion. In order to increase the level of work motivation and job satisfaction of health workers in rural areas, apart from better income, they should get more assistance and support from their supervisors, and awards for good job performance; interpersonal relationships, promotion and advancement opportunities, managerial performance and cooperation at work should be improved; employment security should be provided, as well as more independence at work, with professional supervision of health workers.